WITHDRAWN: Development of improved materials for structural components of sodium-cooled fast reactors. (February 2020) - Bhaduri, A.K.; Laha, K.; Ganesan, V.; Sakthivel, T.; Nandagopal, M.; Prasad Reddy, G.V.; Ganesh Kumar, J.; Vijayanand, V.D.; Panneer Selvi, S.; Srinivasan, G.; Das, Chitta Ranjan; Nagesha, A.; et al.
Abstract : This article has been withdrawn at the request of the author(s) and/or editor. The Publisher apologizes for any inconvenience this may cause. The full Elsevier Policy on Article Withdrawal can be found at http://www.elsevier.com/locate/withdrawalpolicy .